Selection of silicon photomultipliers for a 6LiF:ZnS(Ag) scintillator based cold neutron detector. (4th April 2018) - Osovizky, A; Pritchard, K; Yehuda-Zada, Y; Ziegler, J B; Tsai, P; Ghelman, M; Thompson, A K; Ibberson, R M; Baltic, G M; Majkrzak, C F; Maliszewskyj, N C
Abstract: We describe the process of selecting a silicon photomultiplier (SiPM) as the light sensor for an ultrathin (≈2 mm) highly efficient cold neutron detector. The neutron detector consists of 6 LiF:ZnS(Ag) scintillator in which wavelength shifting (WLS) fibers have been embedded. The WLS fibers conduct the scintillation light out from the scintillator to the SiPM photosensor. In addition to the many benefits of using silicon photomultipliers as photosensors (low cost, compact size, insensitivity to magnetic fields), their selection also presents many challenges (thermally induced dark noise, delayed cross talk, afterpulsing, etc) which are not shared by traditional photomultiplier tubes. In this work, we discuss the considerations for the selection of the appropriate silicon photomultiplier to achieve the best net neutron sensitivity and gamma ray discrimination. Important characteristics for these devices include short recovery time (≈35 ns), high photodetection efficiency (>30% at the target wavelength), low thermal noise (<35 kHz mm −2 at ambient temperatures), and low crosstalk.